2018
DOI: 10.15294/jdm.v9i2.15192
|View full text |Cite
|
Sign up to set email alerts
|

Online Brand Experience: Drivers and Consequences

Abstract: The purpose of this study is to determine the influence of brand involvement, customer-brand engagement, online brand experience to brand satisfaction and brand loyalty of mobile banking applications users in BCA, Bank Mandiri, BRI, and BNI as the big four most valuable brands in Indonesia. This study used primary data sources obtained directly by distributing questionnaires to 260 respondents. The sampling method used is non-probability sampling with purposive sampling technique, and the criteria of responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 29 publications
(56 reference statements)
8
11
0
2
Order By: Relevance
“…Concerning the significant positive direct impact of CBE on online brand experience in the Egyptian banking sector, this study finding matches with the previous studies of and Pratomo and Magetsari (2018) who mentioned that companies must capitalize on brand engagement in fostering a unique online brand experience. CBE in the banking industry helps customers to interact directly with banks through the use of online banking such as internet banking and mobile applications and hence improve customers' online brand experience.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Concerning the significant positive direct impact of CBE on online brand experience in the Egyptian banking sector, this study finding matches with the previous studies of and Pratomo and Magetsari (2018) who mentioned that companies must capitalize on brand engagement in fostering a unique online brand experience. CBE in the banking industry helps customers to interact directly with banks through the use of online banking such as internet banking and mobile applications and hence improve customers' online brand experience.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, it has been showed that the online brand experience has a significant positive direct impact on brand satisfaction in the Egyptian banking sector. This finding was supported by the prior studies of Pratomo and Magetsari (2018) who mentioned that the higher the brand experience achieved by the customer, the higher the level of satisfaction in the banking industry. Besides, other studies such as Chinomona (2013), Kusuma (2014) and stated that the higher the brand experience of a brand, the higher the brand's satisfaction in the eyes of customers.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations